H3K4me3 - dependent epigenetic memory regulates transcriptional reactivation in the oocyte - Navarro-Costa, P. (2016)
SELECTED ORAL COMMUNICATIONS, SESSION 52: EPIGENETIC PATTERN IN OOCYTE AND EMBRYO, Tuesday 16 June 2015. This article/study appears in: Abstract book of the 31st ESHRE Annual Meeting, Lisbon, Portugal, 14-17 June 2015.